Hardening resin composition
By using a revisible resin composition that does not contain or contains less than 50% of the polymer with four or more repeat units, the problem of insufficient light scattering performance and uniformity of the light scattering layer in the LED device is solved, and excellent light scattering performance and uniformity after light curing is achieved.
Patent Information
- Application Number
- JP2024543045
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-30
- Filing Date
- 2024-03-29
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2044-03-29
AI Technical Summary
In existing light emitting diode (LED) devices, the light scattering performance and uniformity of the light scattering layer are difficult to meet the needs of high-quality image display.
Revisible resin compositions are employed that contain no or contain less than 50% of polymers of four or more repeat units, which have a haze of 1.0% or less before photocuring and a haze range of 5.0% to 99.0% after photocuring.
The retardable resin composition has excellent light scattering performance and uniformity after photocuring, and is suitable for various applications, and has good coating performance and photocuring performance.
Smart Images

Figure 0007663789000001 
Figure 0007663789000002 
Figure 0007663789000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition. [Background technology]
[0002] Light-emitting diodes (LEDs) have low power consumption and a long life span, and therefore are widely used in display devices, etc. In recent years, display devices that are capable of displaying high-quality images by mounting LED chips that use tiny LEDs called micro LEDs have been attracting attention (for example, Patent Document 1, etc.). Devices using LEDs face the challenge of improving the light extraction efficiency and uniformity. In particular, in the case of converting monochromatic LED light, a layer that diffuses the light (light diffusion layer) is required to guide the light emitted from the light source uniformly to the color conversion layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-212694 A Summary of the Invention [Problem to be solved by the invention]
[0004] The light diffusion layer is usually formed by applying a curable resin composition with a coating device and then curing the composition. Therefore, the curable resin composition used in the light diffusion layer is required to have excellent coatability, curability, and light diffusion properties after curing. An object of the present invention is to provide a curable resin composition that has excellent coatability and curability, and also has excellent light diffusibility after curing. [Means for solving the problem]
[0005] Disclosure 1 is a curable resin composition containing a polymerizable monomer, which does not contain a polymer having 4 or more repeating units, or the content of polymers having 4 or more repeating units in the curable resin composition is 50 mass% or less, and a coating film of the curable resin composition having a thickness of 30 μm before curing has a haze of 1.0% or less as measured in accordance with JIS K 7136, and a cured product of the curable resin composition having a thickness of 30 μm has a haze of 5.0% or more and 99.0% or less as measured in accordance with JIS K 7136. The present disclosure 2 is the curable resin composition of the present disclosure 1, wherein the polymerizable monomer includes an aliphatic monomer not having an alicyclic skeleton and an aromatic monomer, and a maximum difference in solubility parameter between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer is 1.5 or more. The present disclosure 3 is the curable resin composition according to the present disclosure 1 or 2, wherein the polymerizable monomer includes an aliphatic monomer having no alicyclic skeleton and an aromatic monomer, and a maximum difference in dispersion term ΔD of Hansen solubility parameters between the aliphatic monomer having no alicyclic skeleton and the aromatic monomer is 1.4 or more. The present disclosure 4 is the curable resin composition according to the present disclosure 1, 2, or 3, wherein the polymerizable monomer includes an aliphatic monomer having no alicyclic skeleton and an aromatic monomer, and a maximum difference in polar term ΔP of Hansen solubility parameters between the aliphatic monomer having no alicyclic skeleton and the aromatic monomer is 1.3 or more. The present disclosure 5 is the curable resin composition according to the present disclosure 1, 2, 3, or 4, wherein the polymerizable monomer includes an aliphatic monomer having no alicyclic skeleton and an aromatic monomer, and a maximum difference in hydrogen bond term δH of Hansen solubility parameters between the aliphatic monomer having no alicyclic skeleton and the aromatic monomer is 1.2 or more. The present disclosure 6 is the curable resin composition according to the present disclosure 1, 2, 3, 4, or 5, wherein the polymerizable monomer includes an aliphatic monomer not having an alicyclic skeleton and an aromatic monomer, and a maximum difference in refractive index between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer is 0.07 or more. The present disclosure 7 is the curable resin composition according to the present disclosure 2, 3, 4, 5, or 6, wherein the polymerizable monomer further includes an aliphatic monomer having an alicyclic skeleton. The present invention will be described in detail below.
[0006] The present inventors have investigated the control of the haze before and after curing of a curable resin composition containing a polymerizable monomer, by making the composition contain no or almost no oligomer or polymer component, and have found that a curable resin composition having excellent coatability and curability and excellent light diffusion after curing can be obtained, thereby completing the present invention.
[0007] The curable resin composition of the present invention has a haze of 1.0% or less (hereinafter, also referred to as "haze before curing") measured according to JIS K 7136 for a coating film of the curable resin composition having a thickness of 30 μm before curing. When the haze before curing is 1.0% or less, the curable resin composition of the present invention has excellent photocurability. The preferred upper limit of the haze before curing is 0.02%. The lower the haze before curing, the more preferable, and it is most preferable that the haze is 0%. The haze before curing is measured by the following method. That is, first, the curable resin composition is applied to a 0.7 mm thick non-alkali glass substrate using a spin coater to form a coating film of 30 μm thickness, and a test piece is obtained. The obtained test piece is irradiated with light having a wavelength of 400 to 700 nm from the coating film side of the curable resin composition using a haze meter, and the haze before curing is measured according to JIS K 7136. For example, AN10 (manufactured by AGC) can be used as the non-alkali glass substrate, and COH7700 (manufactured by Nippon Denshoku Industries Co., Ltd.) can be used as the haze meter.
[0008] The curable resin composition of the present invention has a haze (hereinafter also referred to as "haze after curing") of 5.0% or more and 99.0% or less for a 30 μm-thick cured product of the curable resin composition measured in accordance with JIS K 7136. By adjusting the haze after curing to fall within this range, the curable resin composition of the present invention can be suitably used for various applications. The haze after curing is measured by the following method. That is, the curable resin composition is first applied to a non-alkali glass substrate having a thickness of 0.7 mm using a spin coater to form a coating film having a thickness of 30 μm. The obtained coating film is then irradiated with a metal halide lamp having a wavelength of 365 nm and an illuminance of 100 mW / cm. 2 The curable resin composition is cured by irradiating the cured resin composition with ultraviolet light of 400 to 700 nm for 30 seconds, and then heated in an oven at 80° C. for 30 minutes to obtain a test piece having a cured product with a thickness of 30 μm. The obtained test piece is irradiated with light of 400 to 700 nm wavelength from the side of the cured product of the curable resin composition using a haze meter, and the haze after curing is measured according to JIS K 7136. As the non-alkali glass substrate, for example, AN10 (manufactured by AGC Co., Ltd.) can be used, and as the haze meter, for example, COH7700 (manufactured by Nippon Denshoku Industries Co., Ltd.) can be used.
[0009] The haze before curing and the haze after curing can be set within the above-mentioned ranges by adjusting the types and contents of the polymerizable monomer and other components contained in the curable resin composition of the present invention.
[0010] The curable resin composition of the present invention contains a polymerizable monomer. The polymerizable monomer means a monomer having a polymerizable group. Examples of the polymerizable group include a cationic polymerizable group, a radical polymerizable group, etc. Among these, a cationic polymerizable group is preferable, and an epoxy group and an oxetanyl group are more preferable.
[0011] The polymerizable monomer preferably contains an aliphatic monomer having no alicyclic skeleton and an aromatic monomer. By containing the aliphatic monomer having no alicyclic skeleton and the aromatic monomer, the curable resin composition of the present invention can easily adjust the haze before curing, the haze after curing, and the viscosity described below. In particular, the aliphatic monomer having no alicyclic skeleton and the aromatic monomer form a phase separation structure when polymerized by light irradiation, making it easier to set the haze after curing to the above-mentioned range.
[0012] The maximum difference in solubility parameters between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer (hereinafter also referred to as the "maximum difference in SP value") is preferably 1.5 or more. When the maximum difference in SP value is 1.5 or more, the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer are easily formed into a phase separation structure when polymerized by light irradiation, so that it is easier to set the haze after curing to the above range. A more preferable lower limit of the maximum difference in SP value is 1.9. Although there is no particular preferred upper limit to the maximum difference in the SP values, the substantial upper limit is 10.0. In this specification, the solubility parameter (SP value) is the Hansen solubility parameter, which can be derived by calculation from the structural formula using HSP software. As the HSP software, Hansen Solubility Parameter in Practice (HSPiP) can be used. In addition, the maximum difference in SP value means the larger value of a and b, where a is the absolute difference between the SP value of the aliphatic monomer having the maximum SP value among the aliphatic monomers not having an alicyclic skeleton and the SP value of the aromatic monomer having the minimum SP value, and b is the absolute difference between the SP value of the aliphatic monomer having the minimum SP value among the aliphatic monomers not having an alicyclic skeleton and the SP value of the aromatic monomer having the maximum SP value.
[0013] The maximum difference in the dispersion term δD of the Hansen solubility parameters between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer (hereinafter also referred to as the "maximum difference in δD") is preferably 1.4 or more. When the maximum difference in δD is 1.4 or more, the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer are easily polymerized by light irradiation to form a phase separation structure, so that it is easier to set the haze after curing to the above range. A more preferable lower limit of the maximum difference in δD is 3.2. Although there is no particular preferred upper limit to the maximum difference in ΔD, the substantial upper limit is 5.0. The ΔD can be derived from the structural formula by calculation using the above-mentioned HSP software. The maximum difference in ΔD means the larger of c and d, where c is the absolute difference between the ΔD of the aliphatic monomer having the largest ΔD among the aliphatic monomers not having an alicyclic skeleton and the ΔD of the aromatic monomer having the smallest ΔD, and d is the absolute difference between the ΔD of the aliphatic monomer having the smallest ΔD among the aliphatic monomers not having an alicyclic skeleton and the ΔD of the aromatic monomer having the largest ΔD.
[0014] The maximum difference in polarity term ΔP of the Hansen solubility parameters between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer (hereinafter also referred to as the "maximum difference in ΔP") is preferably 1.3 or more. When the maximum difference in ΔP is 1.3 or more, the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer are easily polymerized by light irradiation to form a phase separation structure, so that it is easier to set the haze after curing to the above range. A more preferable lower limit of the maximum difference in ΔP is 1.5. Although there is no particular preferred upper limit to the maximum difference in ΔP, the substantial upper limit is 5.0. The ΔP can be derived from the structural formula by calculation using the above-mentioned HSP software. The maximum difference in ΔP means the larger value of e and f, where e is the absolute difference between the ΔP of the aliphatic monomer having the largest ΔP among the aliphatic monomers not having an alicyclic skeleton and the ΔP of the aromatic monomer having the smallest ΔP, and f is the absolute difference between the ΔP of the aliphatic monomer having the smallest ΔP among the aliphatic monomers not having an alicyclic skeleton and the ΔP of the aromatic monomer having the largest ΔP.
[0015] The maximum difference in hydrogen bond term δH of the Hansen solubility parameters between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer (hereinafter also referred to as "maximum difference in δH") is preferably 1.2 or more. When the maximum difference in δH is 1.2 or more, the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer are easily polymerized by light irradiation to form a phase separation structure, so that it is easier to set the haze after curing to the above range. A more preferable lower limit of the maximum difference in δH is 1.6. Although there is no particular preferred upper limit to the maximum difference in ΔH, the substantial upper limit is 5.0. The δH can be derived from the structural formula by calculation using the above-mentioned HSP software. The maximum difference in δH means the larger of g and h, where g is the absolute difference between the δH of the aliphatic monomer having the largest δH among the aliphatic monomers not having an alicyclic skeleton and the δH of the aromatic monomer having the smallest δH, and h is the absolute difference between the δH of the aliphatic monomer having the smallest δH among the aliphatic monomers not having an alicyclic skeleton and the δH of the aromatic monomer having the largest δH.
[0016] The maximum difference in refractive index between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer (hereinafter also referred to as "maximum difference in refractive index") is preferably 0.07 or more. By making the maximum difference in refractive index 0.07 or more, it becomes easier to set the haze after curing to the above range. A more preferable lower limit of the maximum difference in refractive index is 0.14. Although there is no particular preferred upper limit to the maximum difference in the refractive index, the substantial upper limit is 0.30. In this specification, the refractive index refers to the refractive index relative to the sodium D line measured at 25° C. using an Abbe refractometer. As the Abbe refractometer, for example, a Universal Abbe refractometer ER-7MW (manufactured by ERMA) can be used. In addition, the maximum difference in refractive index refers to the larger value of i and j, where i is the absolute difference between the refractive index of the aliphatic monomer having the maximum refractive index and the refractive index of the aromatic monomer having the minimum refractive index, and j is the absolute difference between the refractive index of the aliphatic monomer having the minimum refractive index and the refractive index of the aromatic monomer having the maximum refractive index.
[0017] Examples of the aliphatic monomer having no alicyclic skeleton include an aliphatic epoxy compound having no alicyclic skeleton, and an aliphatic oxetane compound having no alicyclic skeleton. Examples of the aliphatic epoxy compound not having an alicyclic skeleton include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and trimethylolpropane triglycidyl ether. Examples of the aliphatic oxetane compound not having an alicyclic skeleton include 3-ethyl-3-((2-ethylhexyloxy)methyl)oxetane, 3-ethyl-3-(4-hydroxybutyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(((3-ethyloxetan-3-yl)methoxy)methyl)oxetane, and 3-ethyl-3-((3-(triethoxysilyl)propoxy)methyl)oxetane.
[0018] The content of the aliphatic monomer not having an alicyclic skeleton in 100 parts by mass of the polymerizable monomer is preferably 10 parts by mass at the lower limit and 90 parts by mass at the upper limit. By the content of the aliphatic monomer not having an alicyclic skeleton being within this range, it becomes easier to set the haze after curing within the above range. The content of the aliphatic monomer not having an alicyclic skeleton is more preferably 30 parts by mass at the lower limit and 70 parts by mass at the upper limit.
[0019] Examples of the aromatic monomer include aromatic epoxy compounds and aromatic oxetane compounds. Examples of the aromatic epoxy compound include 4-tert-butylphenyl glycidyl ether, o-phenylphenol glycidyl ether, bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, and bisphenol E type epoxy compounds. Examples of the aromatic oxetane compound include phenoxymethyloxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 1,4-bis(((3-ethyl-3-oxetanyl)methoxy)methyl)benzene, 4,4-bis((3-ethyl-3-oxetanyl)methoxymethyl)biphenyl, and bis((3-ethyl-3-oxetanylmethyl)isophthalate).
[0020] The aromatic monomer content in 100 parts by mass of the polymerizable monomer is preferably 10 parts by mass at the lower limit and 90 parts by mass at the upper limit. By making the aromatic monomer content within this range, it becomes easier to make the haze after curing within the above range. The aromatic monomer content is more preferably 30 parts by mass at the lower limit and 70 parts by mass at the upper limit.
[0021] The polymerizable monomer preferably further contains an aliphatic monomer having an alicyclic skeleton. By containing the aliphatic monomer having an alicyclic skeleton, the obtained curable resin composition has better curability. In addition, by containing the aliphatic monomer having an alicyclic skeleton, phase separation of the polymerizable monomer in the curable resin composition before curing is less likely to occur, so that the obtained curable resin composition has excellent storage stability. Incidentally, a polymerizable monomer having an alicyclic skeleton and an aromatic ring is regarded as the above-mentioned aromatic monomer.
[0022] Examples of the aliphatic monomer having an alicyclic skeleton include an aliphatic epoxy compound having an alicyclic skeleton, and an aliphatic oxetane compound having an alicyclic skeleton. Examples of the aliphatic epoxy compound having an alicyclic skeleton include alicyclic epoxy-modified silicone compounds, dicyclopentadiene-type epoxy compounds, 3,4-epoxycyclohexylmethyl(3,4-epoxy)cyclohexanecarboxylate, and 4,4'-bis(1,2-epoxycyclohexane). Examples of the aliphatic oxetane compound having an alicyclic skeleton include 3-(cyclohexyloxy)methyl-3-ethyloxetane, 2-cyclohexyloxetan-3-one, and the like.
[0023] The content of the aliphatic monomer having an alicyclic skeleton in 100 parts by mass of the polymerizable monomer is preferably 3 parts by mass at the lower limit and 40 parts by mass at the upper limit. By the content of the aliphatic monomer having an alicyclic skeleton being within this range, the obtained curable resin composition has better curability and light diffusion properties after curing. The content of the aliphatic monomer having an alicyclic skeleton is more preferably 5 parts by mass at the lower limit and 30 parts by mass at the upper limit.
[0024] The preferred lower limit of the content of the polymerizable monomer in the curable resin composition of the present invention is 60% by mass, and the preferred upper limit is 95% by mass. By having the content of the polymerizable monomer in this range, the obtained curable resin composition has better coatability, curability, and light diffusion after curing. The more preferred lower limit of the content of the polymerizable monomer is 70% by mass, and the more preferred upper limit is 80% by mass.
[0025] The curable resin composition of the present invention preferably further contains a photopolymerization initiator. Examples of the photopolymerization initiator include a photocationic polymerization initiator, a photoradical polymerization initiator, etc. Among them, it is preferable to use the photocationic polymerization initiator in combination with a polymerizable monomer having a cationically polymerizable group as the polymerizable monomer.
[0026] The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid upon irradiation with light, and may be an ionic photoacid generating type or a nonionic photoacid generating type.
[0027] The anion portion of the ionic photoacid generating cationic photopolymerization initiator is, for example, BF4 - , PF6 - , SbF6 - , (BX4) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups). The anion moiety may be PF m (C n F 2n+1 ) 6-m - (wherein, m is an integer of 0 or more and 5 or less, and n is an integer of 1 or more and 6 or less). Examples of the ionic photoacid generating type photocationic polymerization initiator include aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe salts, and the like, each of which has the anion moiety.
[0028] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonio)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonio)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonio)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate, and triphenylsulfonium hexafluorophosphate. Examples of the sulfonium tetrakis(pentafluorophenyl)borate include triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluorophosphate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluoroantimonate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bistetrafluoroborate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, and tris(4-(4-acetylphenyl)thiophenyl)sulfonium tetrakis(pentafluorophenyl)borate.
[0029] Examples of the aromatic iodonium salt include diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrafluoroborate, and 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate.
[0030] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.
[0031] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrafluoroborate, and 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate.
[0032] Examples of the (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.
[0033] Examples of the nonionic photoacid generating cationic photopolymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, diazonaphthoquinones, and N-hydroxyimide sulfonates.
[0034] Among the above-mentioned photocationic polymerization initiators, commercially available ones include, for example, photocationic polymerization initiators manufactured by Midori Chemical Industry Co., Ltd., photocationic polymerization initiators manufactured by Union Carbide Corporation, photocationic polymerization initiators manufactured by ADEKA Corporation, photocationic polymerization initiators manufactured by 3M Corporation, photocationic polymerization initiators manufactured by BASF Corporation, photocationic polymerization initiators manufactured by Rhodia Corporation, and photocationic polymerization initiators manufactured by San-Apro Corporation. An example of the photocationic polymerization initiator manufactured by Midori Kagaku Co., Ltd. is DTS-200. Examples of the photocationic polymerization initiator manufactured by Union Carbide include UVI6990 and UVI6974. Examples of the photocationic polymerization initiator manufactured by ADEKA Corporation include SP-150 and SP-170. Examples of the photocationic polymerization initiator manufactured by 3M include FC-508 and FC-512. Examples of the cationic photopolymerization initiator manufactured by BASF include IRGACURE261 and IRGACURE290. An example of the cationic photopolymerization initiator manufactured by Rhodia is PI2074. Examples of the photocationic polymerization initiators manufactured by San-Apro include CPI-100P, CPI-200K, CPI-210S, and CPI-410S.
[0035] The preferred lower limit of the content of the photopolymerization initiator relative to 100 parts by mass of the polymerizable monomer is 0.01 parts by mass, and the preferred upper limit is 10 parts by mass. When the content of the photopolymerization initiator is 0.01 parts by mass or more, the obtained curable resin composition has better photocurability. When the content of the photopolymerization initiator is 10 parts by mass or less, the curing reaction of the obtained curable resin composition does not become too fast, and the workability is better, and the cured product can be made more uniform. The more preferred lower limit of the content of the photopolymerization initiator is 0.05 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0036] The curable resin composition of the present invention does not contain a polymer having 4 or more repeating units, or the content ratio of the polymer having 4 or more repeating units in the curable resin composition is 50% by mass or less. Hereinafter, the polymer having 4 or more repeating units is also referred to as an "oligomer or polymer component". When the oligomer or polymer component is contained, a phase separation structure is easily formed after curing, and the obtained cured product is likely to have excellent light diffusion properties, but the viscosity becomes too high and the coating properties are poor. The curable resin composition of the present invention does not contain the oligomer or polymer component, or the content ratio of the oligomer or polymer component is 50% by mass or less, so that the coating properties are excellent while maintaining excellent light diffusion properties after curing. The content ratio of the oligomer or polymer component is more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 1% by mass or less. It is most preferable that the curable resin composition of the present invention does not contain the oligomer or polymer component.
[0037] The curable resin composition of the present invention preferably does not contain a filler, or the content ratio of the filler in the curable resin composition is 20% by mass or less. The curable resin composition of the present invention preferably does not contain the filler, or the content ratio of the filler is 20% by mass or less, so that the obtained curable resin composition has better coatability, and it is easier to adjust the haze before curing to the above-mentioned range. The content ratio of the filler is more preferably 5% by mass or less, further preferably 1% by mass or less, and particularly preferably 0.1% by mass or less. It is most preferable that the curable resin composition of the present invention does not contain the filler.
[0038] The curable resin composition of the present invention may contain various known additives, such as a leveling agent, a sensitizer, a heat curing agent, a silane coupling agent, a plasticizer, a curing retarder, an ultraviolet absorber, an antioxidant, a flame retardant, an antistatic agent, and an antifoaming agent, as necessary, within the scope of not impairing the object of the present invention.
[0039] Examples of a method for producing the curable resin composition of the present invention include a method in which a polymerizable monomer, a photopolymerization initiator, and a leveling agent added as necessary are uniformly mixed using a stirrer.
[0040] The curable resin composition of the present invention has a viscosity at 25° C. of preferably 5.0 mPa·s at lower limit and 100.0 mPa·s at upper limit. When the viscosity at 25° C. is within this range, the curable resin composition of the present invention has better coatability by an inkjet method, etc. The more preferred lower limit of the viscosity at 25° C. is 10.0 mPa·s, and the more preferred upper limit is 50.0 mPa·s. The viscosity can be measured, for example, using a VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer and a No. 1 rotor at a rotation speed of 100 rpm.
[0041] The curable resin composition of the present invention can be cured by irradiation with light. The method for curing the curable resin composition of the present invention by light irradiation may be, for example, a method using a wavelength of 300 nm or more and 400 nm or less and a light irradiation speed of 300 mJ / cm 2 More than 3000mJ / cm 2 Examples of the method include a method of irradiating light with the following integrated amount of light.
[0042] Examples of light sources for irradiating the curable resin composition of the present invention with light include low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, excimer lasers, chemical lamps, black light lamps, microwave excited mercury lamps, metal halide lamps, sodium lamps, halogen lamps, xenon lamps, LED lamps, fluorescent lamps, sunlight, electron beam irradiation devices, etc. These light sources may be used alone or in combination of two or more.
[0043] Examples of the means for irradiating the curable resin composition of the present invention with light include simultaneous irradiation with various light sources, sequential irradiation with a time lag, and a combination of simultaneous irradiation and sequential irradiation. Any irradiation means may be used. Effect of the Invention
[0044] According to the present invention, it is possible to provide a curable resin composition that has excellent coatability and curability, and also has excellent light diffusibility after curing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0046] (Examples 1 to 18, Comparative Examples 1 to 7) The curable resin compositions of Examples 1 to 18 and Comparative Examples 1 to 7 were prepared by stirring and mixing each material using a stirrer according to the compounding ratios shown in Tables 1 to 3. Awatori Rentaro ARE-310 (manufactured by Thinky Corporation) was used as the stirrer. Incidentally, "Actflow BE2" used in Comparative Example 7 is a polymer having 4 or more repeating units.
[0047] (Maximum difference in SP value, maximum difference in δD, maximum difference in δP, and maximum difference in δH) For each polymerizable monomer used in the Examples and Comparative Examples, the SP values, ΔD, ΔP, and ΔH derived using HSPiP, as well as the maximum difference in SP values, the maximum difference in ΔD, the maximum difference in ΔP, and the maximum difference in ΔH calculated from these values, are shown in Tables 1 to 3.
[0048] (Maximum difference in refractive index) The refractive index of each polymerizable monomer used in the Examples and Comparative Examples was measured at 25° C. with an Abbe refractometer (ERMA, "Universal Abbe Refractometer ER-7MW") at sodium D line. The results are shown in Tables 1 to 3. The maximum refractive index differences calculated from the obtained refractive index values are also shown in Tables 1 to 3.
[0049] (Haze before curing) Each of the obtained curable resin compositions was applied to a 0.7 mm thick non-alkali glass substrate (AGC, "AN10") using a spin coater to form a coating film of 30 μm to obtain a test piece. The obtained test piece was irradiated with light having a wavelength of 400 to 700 nm from the coating film side of the curable resin composition using a haze meter (Nippon Denshoku Industries, "COH7700") to measure the haze before curing in accordance with JIS K 7136. The results are shown in Tables 1 to 3.
[0050] (Haze after curing) Each of the obtained curable resin compositions was applied to a 0.7 mm thick non-alkali glass substrate (manufactured by AGC, "AN10") using a spin coater to form a coating film having a thickness of 30 μm. The obtained coating film was irradiated with a metal halide lamp at a wavelength of 365 nm and an illuminance of 100 mW / cm. 2The curable resin composition was cured by irradiating it with ultraviolet light of 400 nm for 30 seconds, and then heated in an oven at 80° C. for 30 minutes to cure the curable resin composition, thereby obtaining a test piece having a cured product of 30 μm in thickness. The obtained test piece was irradiated with light of 400 to 700 nm in wavelength from the side of the curable resin composition cured product using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., "COH7700"), and the haze after curing was measured according to JIS K 7136. The results are shown in Tables 1 to 3.
[0051] <Evaluation> The curable resin compositions obtained in the examples and comparative examples were evaluated by the following methods. The results are shown in Tables 1 to 3.
[0052] (viscosity) The viscosity of each of the obtained curable resin compositions was measured using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., "VISCOMETER TV-22") and a No. 1 rotor at 25° C. and a rotation speed of 100 rpm.
[0053] (curable) The curability was evaluated as follows: when the haze measured in the above "(Haze before curing)" was 1.0 or less, it was rated as "A", and when it exceeded 1.0, it was rated as "B".
[0054] (Light diffusion after curing) The light diffusion property after curing was evaluated based on the following criteria: if the haze measured in the above "(Haze after curing)" was 5.0% or more and 99.0% or less, it was rated as "A", and if it was less than 5.0% or more than 99.0%, it was rated as "B".
[0055] (Storage stability) After preparation, each of the obtained curable resin compositions was stored for 24 hours in an environment of 25° C. and 50% RH. The curable resin compositions after storage were visually observed, and storage stability was evaluated by assigning an "A" to the case where no phase separation was observed and an "B" to the case where phase separation was observed.
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3]
[0059] As shown in Tables 1 to 3 above, the curable resin compositions obtained in Examples 1 to 18 were suitable for inkjet coating, whereas the curable resin composition obtained in Comparative Example 7 was not suitable for inkjet coating because of its extremely high viscosity at 25°C, and could not be coated by the inkjet method. [Industrial Applicability]
[0060] According to the present invention, it is possible to provide a curable resin composition that has excellent coatability and curability, and also has excellent light diffusibility after curing.
Claims
1. A curable resin composition containing a polymerizable monomer, the polymerizable monomer includes an aliphatic monomer having no alicyclic skeleton and an aromatic monomer, the aliphatic monomer not having an alicyclic skeleton includes at least one selected from the group consisting of an aliphatic epoxy compound not having an alicyclic skeleton and an aliphatic oxetane compound not having an alicyclic skeleton, the content of the aliphatic monomer not having an alicyclic skeleton is 30 parts by mass or more and 76 parts by mass or less in 100 parts by mass of the polymerizable monomer, The aromatic monomer includes at least one selected from the group consisting of an aromatic epoxy compound and an aromatic oxetane compound, the content of the aromatic monomer in 100 parts by mass of the polymerizable monomer is 24 parts by mass or more and 70 parts by mass or less, the curable resin composition does not contain a polymer having a repeating unit number of 4 or more, or the content ratio of the polymer having a repeating unit number of 4 or more in the curable resin composition is 50 mass% or less; A coating film of the curable resin composition having a thickness of 30 μm before curing has a haze of 1.0% or less as measured in accordance with JIS K 7136, and a cured product of the curable resin composition having a thickness of 30 μm has a haze of 5.0% or more and 99.0% or less as measured in accordance with JIS K 7136. A curable resin composition comprising:
2. The curable resin composition according to claim 1, wherein the maximum difference in solubility parameter between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer is 1.5 or more.
3. The curable resin composition according to claim 1, wherein the maximum difference in the dispersion term δD of the Hansen solubility parameters between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer is 1.4 or more.
4. The curable resin composition according to claim 1, wherein the maximum difference in polarity term δP of the Hansen solubility parameters between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer is 1.3 or more.
5. The curable resin composition according to claim 1, wherein the maximum difference in the hydrogen bond term δH of the Hansen solubility parameters between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer is 1.2 or more.
6. The curable resin composition according to claim 1, wherein the maximum difference in refractive index between the aliphatic monomer not having an alicyclic skeleton and the aromatic monomer is 0.07 or more.
7. The curable resin composition according to claim 1 , wherein the polymerizable monomer further comprises an aliphatic monomer having an alicyclic skeleton.
Citation Information
Patent Citations
Photopolymerizable composition, photocurable hardenable pressure sensitive adhesive sheet, and bonding of member
JP2000144071A
Display
JP2019212694A
Active energy ray-curable composition for inkjet, cured object, and method for manufacturing cured object
JP2021146710A
Organic electronic device sealing member
WO2015199164A1